IMPLEMENTASI ETIKA PELAYANAN PUBLIK DI KANTOR PERTANAHAN KOTA BENGKULU - Rahman Hadi Eka Putra Putra; Rosidin Rosidin (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2026)
This research is motivated by the importance of public service ethics in improving the quality of transparent and accountable land services. However, there are still problems such as uncertainty of service time and lack of clarity of information at the Bengkulu City Land Office. This research aims to analyze the implementation of public service ethics which includes integrity, responsibility, accountability, and justice. This study uses a qualitative method with a case study approach, involving 9 data informants through interviews, observations, and documentation. The results of the study show that the implementation of public service ethics is quite good in terms of integrity and justice, but it is still not optimal in terms of responsibility and accountability. In conclusion, the implementation of public service ethics still needs to be improved, especially in terms of clarity of information and certainty of service time. Keywords: Public Service Ethics, Integrity, Accountability, Justice